Research on the Training Model of Marketing Professionals under the Background of Internet + Big Data - Ma, Yanyang (2021 International Conference on Artificial Intelligence and Electromechanical Automation (AIEA), 2021)
Marketing is a specialty that closely fits the practice of social development. In order to effectively cultivate high-quality and innovative talents for social needs, colleges and universities should fully and comprehensively grasp the development trend of Internet + big data, and it is effective construct a scientific training system to effectively improve the overall effectiveness of talent training. In the process of cultivating marketing professionals, colleges and universities should fully cater to the development needs of the Internet + big data, effectively construct a refined talent training program, and consolidate the actual results of training.